The use of cold nuclear fusion for heating buildings and structures - E. V. Nazarova; N. Yu. Avetyan (Современная наука и инновации, 2023)
Introduction: The construction of buildings originated with man and developed in the same way. Man created a variety of structures for his being and work, equipping premises to solve certain problems. And, faced with the problems of improvement, he designed new systems, one of the first of these systems was the heating system. It was induced to reproduce and maintain heat in buildings and structures, in order to preserve furniture and other utensils, as well as the health of the person himself. It is difficult to imagine modern residential and non-residential buildings without equipment and appliances that create a comfortable climatic environment. And this branch of engineering systems is developing faster and faster over time. However, not everyone knows that heating buildings and structures can be more profitable.Cold fusion for heating buildings and structures: This paper discusses the use of cold fusion, called cavitation, for heating buildings and structures. An analysis of the types of heat generator was carried out, all the advantages and disadvantages were analyzed. The conditions for the installation and use of cavitation heat generators are also considered.Results: as a result of the work done, it can be concluded that the use of cold nuclear fusion (cavitation) using various types of cavitation heat generators is more cost-effective, environmentally friendly, safe and convenient, in comparison with standard heating equipment. Of the above varieties of heat generators, the most comfortable in terms of use and maintenance was selected. Also, as a result of studying the operation of heat generators, it was concluded that in addition to heating a building or structure, this installation can heat running water used in everyday life for various purposes.Conclusion: It can be concluded that cold nuclear fusion (cavitation) when used in a domestic environment, and more specifically in heating buildings and structures, is not only cheap to install and operate, but also environmentally friendly and safe for human health.